1988
DOI: 10.1039/p29880001823
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of 3-substituted cephalosporins catalysed by β-lactamases I and II from Bacillus cereus and by hydroxide ion

Abstract: Second-order rate constants for the alkaline hydrolysis of 3-thiol substituted cephalosporins are independent of the pK, of the thiol over a pK, range of 9. If there is a leaving group at C-3' it is expelled after the p-lactam ring is opened and the expulsion of the leaving group does not enhance the rate of p-lactam C-N bond fission. The zinc enzyme P-lactamase II is about a 100-fold better catalyst than the serine enzyme P-lactamase I for the hydrolysis of the same cephalosporin. The second-order rate consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…These substituents form good leaving groups during cephalosporin hydrolysis. The kinetic data for the B. cereus enzyme indicated that the rate limiting step in hydrolysis is the formation of the tetrahedral intermediate, rather than the release of the leaving group [47]. Structurally, having an open groove enables the leaving groups to diffuse away from the active site.…”
Section: Proposed Mode Of Binding Of Substratesmentioning
confidence: 99%
“…These substituents form good leaving groups during cephalosporin hydrolysis. The kinetic data for the B. cereus enzyme indicated that the rate limiting step in hydrolysis is the formation of the tetrahedral intermediate, rather than the release of the leaving group [47]. Structurally, having an open groove enables the leaving groups to diffuse away from the active site.…”
Section: Proposed Mode Of Binding Of Substratesmentioning
confidence: 99%
“…However, their "leaving" is not a required precursor to hydrolysis (22), which would give rise to elevated enzyme/substrate concentrations. Evidence for such a complex has been found for the cepham cefoxitin, which does have a leaving group, and is both a poor substrate and has been shown to inhibit the hydrolysis of a reporter substrate by the proposed formation of a stable enzyme/substrate complex (23). Our work would appear to extend these findings to show other similar cephams forming relatively stable complexes.…”
Section: Discussionmentioning
confidence: 50%
“…Different side chains on the 7 position of the cepham core structure have been found to invoke only small changes in K cat /K m values for ␤-lactamase II (24). This may not be true of side chains possessing a 5-membered heterocyclic ring such as oxacillin, as a similar penam, ticarillin, has been found to yield 10 3 times lower K cat /K m values than for good substrates of ␤-lactamase II, although no evidence for a stable enzyme/substrate complex was found (23). The reason for the formation of a more stable complex with oxacillin is still unclear; however, the fact that it was observable by inhibiting binding of IFRN2104 indicates that the Mab may prove useful in the study of kinetics of other ␤-lactams with ␤-lactamase II.…”
Section: Discussionmentioning
confidence: 86%
“…Intramolecular Aminolysis of Thioxocephalosporin. Many cephalosporins ( 1 ) possess a leaving group at C3‘ which is generally expelled after β-lactam ring opening. ,,, However, cephalexin ( 5 ) is a cephalosporin with a methyl group at C3 and with an amino group in the side-chain at C7. It is known that the degradation of cephalexin in water occurs with both hydrolysis and intramolecular aminolysis, the relative importance of which varies with pH .…”
Section: Resultsmentioning
confidence: 99%